Teachers' salaries in Latin America: How much are they (under or over) paid? - Alejandra Mizala; Hugo \~Nopo (Institute for the Study of Labor (IZA), 2011)
This paper documents the extent to which teachers are underpaid vis-à-vis workers in other professional and technical occupations in Latin America circa 2007. These labor earnings differences, attributed to observable socio-demographic and job characteristics, are assessed using a matching methodology (\~Nopo, 2008). Teachers' underpayment is found to be stronger than what has been previously reported in the literature, especially among pre-school and primary teachers. Nonetheless, behind the region averages there is an important cross-country heterogeneity. Teachers' underpayment is more pronounced among males, older workers, household heads, part-timers, formal workers, those who work in the private sector, and (mostly) among those with complete tertiary education. Two amenities of the teaching profession, namely the longer job tenure and the flexible job schedules within the year, are also explored. Even after accounting for the possible compensating differentials of these two amenities, teachers' underpayment vis-à-vis that of other professional and technicians prevail.
urn:nbn:de:101:1-201109297447
Keywords: J31; J44; J8; O54; 330; wage differentials; professional labor markets; Latin America; Lehrkräfte; Lohnstruktur; Vergleich; Privatwirtschaft; Lateinamerika